Problematika Pendaftaran Hak Milik Atas Tanah Yang Menyebabkan Sertifikat Ganda di Kabupaten Tolitoli - Ahmad Malontu (Formosa Journal of Sustainable Research, 2022)
The purpose of this study is to analyze the legal certainty of land rights holders when there are multiple certificates and to analyze the factors that cause double certificates of land rights by the Land Office. The research method used is empirical research method. Data collection techniques are interview and documentation techniques. The types of data sources that the author uses are primary legal materials and secondary legal materials. The purpose of the study was to determine the cause of dual certificate ownership, the stages of the lawsuit settlement process through the State Administrative Court and or the District Court, namely registration of claims, paying the down-payment of court fees, registration of cases, delegation of case files, determination of the panel of judges, determination of trial days, summons of the parties, mediation stage, lawsuit reading stage, answer stage, proof stage, conclusion stage, decision stage, and legal remedies for lawsuits as well as double certificate legal certainty